Ostraka e iscrizioni su ceramica da Efeso tardo-antica - Biagetti, Claudio (Axon, 2019)
This paper provides an overview on the DFG-Project Schriftkultur und Wirtschaftsleben im spätantiken Ephesos. Neue Ostraka und Inschriften auf Gebrauchskeramik. Focus of this project is the study of two groups of potsherds with scratched inscriptions, which have been unearthed in the urban area of Ephesos. Among these findings, a number of ostraka deserve special attention, preserving new details of the social and economic life of the ancient city. These new texts are going to be edited in an open access database and studied in greater detail in a printed volume.